The impact of simulated visual impairment on medication use process: A study with healthy volunteers - Théodora Merenda; Fanny Depasse; Stéphanie Patris (Exploratory Research in Clinical and Social Pharmacy)
Background: Visual impairment may be caused by various diseases and can impact the safe use of medications. It is therefore important that healthcare professionals consider these challenges to facilitate the correct administration of medications by visually impaired patients. Objective: To determine the category of visual impairment beyond which it becomes impossible to identify medication boxes, to read patient information leaflets, expiration dates, and dosage instructions. Methods: Visual impairment was simulated with glasses on healthy volunteers who had to identify and read different elements on medication boxes and leaflets. The participant eligibility was confirmed through the administration of five ophthalmological tests designed to quantify functional vision. Data were analyzed using a within-subject repeated measures ANOVA. Results: Ninety-two simulations were conducted. This study indicates that for a simulated moderate visual impairment, 81 % of participants lacked access to the medication names and doses, 75 % lacked access to the full expiration date, and 60 % were unable to read the leaflets. Additionally, a simulated moderate visual impairment resulted in a reduced reading speed of 44 words per minute. The low contrast of the writing on medication boxes makes identification more difficult. Conclusions: This simulation study demonstrated that it became impossible to identify medication boxes from a severe visual impairment onwards, while it was no longer possible to read leaflets and expiry dates from a moderate visual impairment onwards. Consequently, it is necessary to ensure that the patient has strategies to identify medications, particularly if the packaging exhibits low contrast and small print.